Processo da irrigação localizada utilizando o controle estatístico De qualidade - Andrade, Mauricio Guy de (2016)
For the optimization of irrigation systems, it is necessary to use systems with high uniformity of operation, such as localized irrigation systems, considering drip and micro sprinkler irrigation most notorious. For an effective evaluation of these systems, some parameters are important to be used, such as the Christiansen Uniformity Coefficient (CUC) and the Uniform Distribution Coefficient (DU). A number of factors, including terrain topography, water pumping and emitter spacing influences the uniformity of distribution. In order for these parameters to be evaluated with higher qualification, it is important to use statistical and quality statistical techniques, such as statistical quality control of the process (CSP), through the Shewhart, Exponentially Weighted Moving Average (EWMA) and Cumulative Sum (CUSUM), which allows the monitoring of the irrigation process and the process capacity index (Cp) that determines how much the process meets the required specifications, in this case, the uniformity classifications. Thus, the objective of the research was to evaluate the process of localized irrigation using statistical quality control. The work was divided in three articles, with the specific objectives of evaluating the spacings between microsprinklers; the influence of the use of photovoltaic solar energy on water pumping in the uniformity of distribution in irrigation by micro sprinkler; and the influence of slope and fertilizer use on the uniformity of drip irrigation. Irrigation tests were performed in laboratory, with less influence of climatic factors. In relation to the micro sprinkler method, the smaller spacing presented the highest uniformities of distribution and the use of an energy storage system when using photovoltaic solar energy for water pumping decreases the variability of the uniformity. For the drip irrigation the higher uniformities and with greater control of the process were for the treatments carried out with treated water and the terrain level. For localized irrigation the EWMA control charts are more adequate to diagnose small variations and Shewhart's to diagnose high variations. The increase in Cp is directly proportional to the mean values of CUC and DU. CEP techniques were adequate to evaluate the uniformity of distribution of localized irrigation. In an effort to rationalize the use of water and nutrients and increase uniformity of distribution in localized irrigation, the use of statistical process control techniques are important for proper process monitoring and consequent increase in agricultural productivity.